(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2022)
This article is devoted to the theoretical and experimental study of the change in the temperature and humidity regime in light concretes on porous aggregates for the water absorption of concrete. The obtained data indicate that with an increase in bulk mass and with the use of ordinary sand as a fine aggregate, the water absorption of concretes on the investigated porous aggregates decreases.